GUIDE TO THE DEVELOPMENT OF THE INTENSIVE ENGLISH PROGRAM FOR GRADUATE STUDENTS AT THE SILPAKORN UNIVERSITY IN THAILAND - Sunasuan, Piyawan; Pansuppawat, Thiranan; Manaratchasak, Mananya; Nillapun, Maream (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This research aims to develop a guide to the development of the intensive English program for Graduate students in the study context of reviewing the English intensive courses for graduate students in three institutions: Kent State University, Chulalongkorn University, and Mahidol University, and compare them to the English intensive course in Silpakorn University. The objectives were 1) To study the potential of the current intensive English program with the expected proficiency level 2) To study the English language skills required for the development of the Intensive English Program for Graduate Students at the Silpakorn University in Thailand. The research design followed mixed methods to answer the research questions. The data was collected from both primary data by survey questionnaire with 46 students enrolled in the ENG 102 and ENG 103 courses of the academic year of 2019/2020 in the first semester from the Silpakorn University, Sanamchandra Palace Campus, and secondary data using descriptive research by focus groups discussion with 6 students from the previous group, and interviews with two teachers. The data was collected from 1) student survey 2) teacher interview and 3) focus group discussion, and analyzed by calculating the mean (x̅), the standard deviation, priority needs index (PNI), frequency, and document analysis. According to the research results, the current course only meets the overall expectation at a medium level. The course is found to only focus on passing the standard criteria but does not meet several needs of learners in relevant to academic purposes, communication, and occupational purposes. More program options for specific skills are highly recommended including academic writing skills, reading skills at a practical level, writing skills for occupational purposes, reading skills for occupational purposes, speaking skills for academic purposes, and listening skills for occupational purposes.